EUROPIUM RETENTION ONTO CLAY MINERALS FROM 25 TO 150 °C: EXPERIMENTAL MEASUREMENTS, SPECTROSCOPIC FEATURES AND SORPTION MODELLING - Tertre E.; Berger G.; Castet S.; Loubet M.; Giffaut E.; Simoni E.; Catalette H. (My University, 2006)
The sorption of Eu(III) onto kaolinite and montmorillonite was investigated up to 150 °C. The clays were purified samples, saturated with Na in the case of montmorillonite. Batch experiments were conducted at 25, 40, 80 and 150 °C in 0.5 M NaClO4 solutions to measure the distribution coefficients (Kd) of Eu as a trace element (<10-6 mol/L) between the solution and kaolinite. For the Na-montmorillonite, we used Kd results from a previous study [Tertre, E., Berger, G., Castet, S., Loubet, M., Giffaut, E., 2005. Experimental study of adsorption of Ni2+, Cs+ and Ln3+ onto Na-montmorillonite up to 150 °C. Geochim. Cosmochim. Acta 69, 4937-4948] obtained under exactly the same conditions. The number and nature of the Eu species sorbed onto both clay minerals were investigated by time resolved laser fluorescence spectroscopy (TRLFS) in specific experiments in the same temperature range. We identified a unique inner-sphere complex linked to the aluminol sites in both clays, assumed to be {double bond, long}AlOEu2+ at the edge of the particles, and a second exchangeable outer-sphere complex for montmorillonite, probably in an interlayer position. The Kd values were used to adjust the parameters of a surface complexation model (DLM: diffuse layer model) from 25 to 150 °C. The number of Eu complexes and the stoichiometry of reactions were constrained by TRLFS. The acidity constants of the amphoteric aluminol sites were taken from another study [Tertre, E., Castet, S., Berger, G., Loubet, M., Giffaut, E. Acid/base surface chemistry of kaolinite and Na-montmorillonite at 25 and 60 °C: experimental study and modelling. Geochim. Cosmochim. Acta, in press], which integrates the influence of the negative structural charge of clays on the acid/base properties of edge sites as a function of temperature and ionic strength. The results of the modelling show that the observed shift of the sorption edge towards low pH with increasing temperature results solely from the contribution of the {double bond, long}AlOEu2+ edge complexes. Finally, we successfully tested the performance of our model by confronting the predictions with experimental Kd data. We used our own data obtained at lower ionic strength (previous study) or higher suspension density and higher starting concentration (TRLFS runs, this study), as well as published data from other experimental studies [Bradbury, M.H., Baeyens, B., 2002. Sorption of Eu on Na and Ca-montmorillonite: experimental investigations and modeling with cation exchange and surface complexation. Geochim. Cosmochim. Acta 66, 2325-2334; Kowal-Fouchard, A., 2002. Etude des mécanismes de rétention des ions U(IV) et Eu(III) sur les argiles: influence des silicates. Ph.D. Thesis, Université Paris Sud, France, 330p]. © 2006 Elsevier Inc. All rights reserved.